Factors Shaping Students' Love of Money: Gender, Socioeconomic Status, Education, and Work Experience: Faktor-Faktor yang Membentuk Kecintaan Mahasiswa terhadap Uang: Jenis Kelamin, Status Sosial Ekonomi, Pendidikan, dan Pengalaman Kerja - Marita, Dea Putri; Abidin, Fityan Izza Noor (Indonesian Journal of Law and Economics Review, 2024)
Love of money plays a significant role in shaping financial behavior, particularly among students in the field of accounting. However, there is limited research examining how factors such as gender, socio-economic status, education level, and work experience influence this attitude. This study aims to fill this knowledge gap by investigating the influence of these variables on love of money among accounting students. Employing a quantitative approach, data were collected from a sample of 187 students from the class of 2020-2021. The research findings reveal that gender (X1), socio-economic status (X2), education level (X3), and work experience (X4) all have a statistically significant effect on love of money, with a significance value (sig) of less than 0.05 for each variable. The novelty of this study lies in its comprehensive analysis of multiple socio-demographic factors influencing love of money. Implications of these findings suggest the need for educators and policymakers to consider these factors when developing financial literacy programs, aiming to foster a balanced financial mindset in students. Highlights: Significant Influence: Gender, socio-economic status, education, and work experience affect love of money. Quantitative Study: Research conducted using a sample of 187 accounting students. Implications: Findings guide financial literacy program development for students. Keywords: Love of Money, Gender, Socio-Economic Status, Education Level, Work Experience